Postpartum primipar kadınlarda travmatik stres ve depresyon düzeyine sosyal desteğin etkisi - Cin, Befrin (My University, 2022)
Araştırma postpartum primipar kadınlarda travmatik stres ve depresyon düzeyine sosyal desteğin etkisini belirlemek amacı ile yapılmıştır

The present study was carried out in order to identify the effect of social support on traumatic stress and depression levels for postpartum primiparous women.
Keywords: depression; depresyon; Kadınlar; Postpartum; psikotravma; psycho-trauma; Social service; social support; sosyal desteK Postpartum; Sosyal hizmet; stres; stress; Turkey; Türkiye; Women